1990
DOI: 10.1111/j.1476-5381.1990.tb14125.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in histamine receptors of guinea‐pig ileal smooth muscle produced during agonist‐induced desensitization

Abstract: 1 The effects of prolonged treatment with histamine (10-4M, 30min) on desensitization at histamine H -receptors of guinea-pig ileal longitudinal muscle were investigated. 2 This treatment did not change either the maximum amount or dissociation constant (Kd) of [3H]-mepyramine binding to membranes of guinea-pig ileal muscle. 3 In contrast, this treatment shifted the histamine inhibition curves of [3H]-mepyramine binding to the right both in the presence and absence of 0.5 mm guanosine-5'-triphosphate (GTP). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the intestine, there is evidence that histamine receptor desensitization after prolonged application of histamine is not likely to occur in vivo ( Tamura & Wood, 1992 ) although such a desensitization is reported repeatedly in in vitro intestinal preparations (for instance: Bielkiewicz & Cook, 1984 ; Hishinuma & Uchida, 1988 ; Horio et al ., 1990 ; Perez‐Garcia et al ., 1998 ). Specifically for the histamine H 1 receptor it is shown that desensitization results from a reduced affinity of the receptor for histamine ( Horio et al ., 1990 ) and from the internalization of the H 1 receptor ( Hishinuma & Young, 1995 ) which may explain why the histamine receptor antagonists had no effect on the contractions to cholinergic nerve stimulation during chronic inflammation. The sensitivity to desensitization of the H 1 receptor may also depend upon the precise location of the receptor since we noticed that the direct contractile effect of 100 μ M histamine on the smooth muscle was preserved in chronically inflamed ileum whereas the neuronally‐mediated inhibitory effect of histamine on cholinergic nerve activity was lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the intestine, there is evidence that histamine receptor desensitization after prolonged application of histamine is not likely to occur in vivo ( Tamura & Wood, 1992 ) although such a desensitization is reported repeatedly in in vitro intestinal preparations (for instance: Bielkiewicz & Cook, 1984 ; Hishinuma & Uchida, 1988 ; Horio et al ., 1990 ; Perez‐Garcia et al ., 1998 ). Specifically for the histamine H 1 receptor it is shown that desensitization results from a reduced affinity of the receptor for histamine ( Horio et al ., 1990 ) and from the internalization of the H 1 receptor ( Hishinuma & Young, 1995 ) which may explain why the histamine receptor antagonists had no effect on the contractions to cholinergic nerve stimulation during chronic inflammation. The sensitivity to desensitization of the H 1 receptor may also depend upon the precise location of the receptor since we noticed that the direct contractile effect of 100 μ M histamine on the smooth muscle was preserved in chronically inflamed ileum whereas the neuronally‐mediated inhibitory effect of histamine on cholinergic nerve activity was lost.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that the direct smooth muscle contraction to 10 mM histamine was lower in chronically in¯amed ileum points towards a diminished reactivity of histamine receptors to exogenous histamine. In the intestine, there is evidence that histamine receptor desensitization after prolonged application of histamine is not likely to occur in vivo (Tamura & Wood, 1992) although such a desensitization is reported repeatedly in in vitro intestinal preparations (for instance: Bielkiewicz & Cook, 1984;Hishinuma & Uchida, 1988;Horio et al, 1990;Perez-Garcia et al, 1998). Speci®cally for the histamine H 1 receptor it is shown that desensitization results from a reduced anity of the receptor for histamine (Horio et al, 1990) and from the internalization of the H 1 receptor (Hishinuma & Young, 1995) which may explain why the histamine receptor antagonists had no eect on the contractions to cholinergic nerve stimulation during chronic in¯ammation.…”
Section: Histamine Receptorsmentioning
confidence: 99%
“…These results suggest that longer time periods of agonist treatment may not necessarily develop heterologous desensitization, as reported for cholecystokinin‐induced progression from homologous to heterologous desensitization of contraction in the guinea‐pig stomach 10 . It has been reported that histamine induces heterologous desensitization in the guinea‐pig ileum, 11 BC3H‐1 muscle cells, 12 DDT 1 MF‐2 smooth muscle cells, 13 Chinese hamster ovary (CHO) cells 14 and GT1‐7 neuronal cells, 15 but not in the guinea‐pig jejunum 16 and lung, 17 mouse cerebral cortex, 18 HeLa cells, 19 human umbilical vein endothelial cells 20 and 1321 N1 human astrocytoma cells 21 . It is possible that heterologous aspects of histamine‐induced desensitization may become apparent depending on the developmental stage of desensitization examined, as was the case in our studies 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…where B represents specific [3H]mepyramine binding, B, , maximum binding of [3H]mepyramine, I the concentration of the inhibitor drug, IC50 the concentration of the inhibitor drug inducing half-maximum inhibition of [3H]mepyramine binding, and n the Hill coefficient. The best-fit values of n were obtained by a non-linear least-squares curve-fitting procedure-the program was implemented on a PC-9800 (NEC, Japan) microcomputer system using the simplex method (Nelder & Need 1965) as previously described (Horio et al 1990b). The dissociation constants (Ki) were calculated from IC50 values according to the equation of Cheng & F'rusoff (1973).…”
Section: Measurement Of ['Hlmepyramine Bindingmentioning
confidence: 99%